Al-Qur’an dan Penyimpangan Religiusitas: Studi Analisis Pemikiran Charles Kimball - Alfarikhah, Ita; Safei, Abdullah; Ariyadi, Samsul (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This research aims to examine the concept of religious deviance from the Qur’anic perspective and analyze its relevance to Charles Kimball’s ideas on the dangers of religion. The main focus of this study is to explore how the Qur’an views the phenomenon of religious deviation that arises in religious practices, and to what extent this concept aligns or contrasts with Kimball’s five indicators of religious danger, namely absolute truth claims, blind obedience, the pursuit of an ideal age, justification of any means, and calls for holy war. This research employs a qualitative approach using thematic interpretation (tafsir maudhu‘i), content analysis, and a comparative analysis of Kimball’s thought. The primary sources of the study include the Qur’an, both classical and contemporary tafsir particularly Tafsir al-Munir by Wahbah al-Zuhaili and Kimball’s work When Religion Becomes Evil. The findings reveal that the Qur’an firmly condemns all forms of religious deviation characterized by the misuse of religious authority, excessive fanaticism, intolerance, and the manipulation of sacred teachings for worldly or political purposes. The Qur’an emphasizes the importance of maintaining a balance between faith, reason, and morality as the foundation of true religiosity, warning that distortion in these three aspects may lead to polytheism, hypocrisy, and disbelief. Kimball’s ideas share common ground with the Qur’anic perspective in criticizing fanaticism and violence in the name of religion; however, the Qur’an provides a more comprehensive normative foundation through the principles of tawhid (divine unity) and rahmatan lil ‘alamin (mercy to all creation). Therefore, this study concludes that preventing religious deviance can only be achieved through a holistic understanding of the Qur’an that harmonizes theological, ethical, and social dimensions in religious life.